1993
DOI: 10.1227/00006123-199312000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Parameters in Patients with Acute Cervical Cord Trauma

Abstract: The cardiovascular response of the patient with acute spinal cord injury (SCI) is known to be altered secondary to the cord injury. Our current protocol of managing the acute phase of patients with SCI includes invasive hemodynamic monitoring (with arterial line and Swan-Ganz catheter) and support with fluids and dopamine and/or dobutamine, titrated to maintain a hemodynamic profile with adequate cardiac output (to be determined by oxygen consumption and delivery) and a mean blood pressure of > 90 mm Hg. We fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(118 citation statements)
references
References 16 publications
1
112
0
5
Order By: Relevance
“…Acute spinal surgery, within the first 24 h following SCI, to alleviate mechanical shearing and compression forces is used to restrict primary damage to the cord, as well as secondary damage that can result from extended periods of compression [13]. In addition to spinal cord stabilization, arterial oxygenation and maintenance of mean arterial blood pressure between 85 and 90 mm Hg following acute SCI is vital in reducing secondary damage due to ischemia and hypoxia, and improving functional outcome [11,[14][15][16][17][18]. Hypothermia is also currently in clinical testing as a means of limiting secondary damage immediately following injury [19,20].…”
Section: Clinical Treatmentmentioning
confidence: 99%
“…Acute spinal surgery, within the first 24 h following SCI, to alleviate mechanical shearing and compression forces is used to restrict primary damage to the cord, as well as secondary damage that can result from extended periods of compression [13]. In addition to spinal cord stabilization, arterial oxygenation and maintenance of mean arterial blood pressure between 85 and 90 mm Hg following acute SCI is vital in reducing secondary damage due to ischemia and hypoxia, and improving functional outcome [11,[14][15][16][17][18]. Hypothermia is also currently in clinical testing as a means of limiting secondary damage immediately following injury [19,20].…”
Section: Clinical Treatmentmentioning
confidence: 99%
“…Similarly, Levi et al 26 reported on 50 patients with an acute SCI. The maps of all these patients was kept above 90 mm Hg, and 42% demonstrated clinical recovery.…”
Section: Discussionmentioning
confidence: 92%
“…Two studies have demonstrated improved neurologic function and a decrease in mortality in SCI patients who were kept relatively hypertensive. 26,27 Although no consensus has been established on the exact target blood pressure or treatment duration necessary, clinical protocols often aim to keep the mean arterial pressure (MAP) above 85 mm Hg or 90 mm Hg for between 5 and 7 days after injury. [26][27][28] Whereas a MAP of 85-90 mm Hg is an acceptable baseline number, this goal may need to be modified based on patient factors such as preexisting HTN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that maintenance of an MAP within normal range may play a neuroprotective role in the acute phase. 6 However, this can be done with other means that will not put the patient at risk of overhydration. Moreover, it was previously reported that the most significant predictor of hyponatremia in individuals with SCI is the level and the severity of the injury.…”
Section: Discussionmentioning
confidence: 99%